Biosynthesis and Characterization of Silver Nanoparticles by Aspergillus Species. (29th August 2016) - Zomorodian, Kamiar; Pourshahid, Seyedmohammad; Sadatsharifi, Arman; Mehryar, Pouyan; Pakshir, Keyvan; Rahimi, Mohammad Javad; Arabi Monfared, Ali
Abstract : Currently, researchers turn to natural processes such as using biological microorganisms in order to develop reliable and ecofriendly methods for the synthesis of metallic nanoparticles. In this study, we have investigated extracellular biosynthesis of silver nanoparticles using four Aspergillus species including A. fumigatus, A. clavatus, A. niger, and A. flavus . We have also analyzed nitrate reductase activity in the studied species in order to determine the probable role of this enzyme in the biosynthesis of silver nanoparticles. The formation of silver nanoparticles in the cell filtrates was confirmed by the passage of laser light, change in the color of cell filtrates, absorption peak at 430 nm in UV-Vis spectra, and atomic force microscopy (AFM). There was a logical relationship between the efficiencies of studied Aspergillus species in the production of silver nanoparticles and their nitrate reductase activity. A. fumigatus as the most efficient species showed the highest nitrate reductase activity among the studied species while A. flavus exhibited the lowest capacity in the biosynthesis of silver nanoparticles which was in accord with its low nitrate reductase activity. The present study showed that Aspergillus species had potential for the biosynthesis of silver nanoparticles depending on their nitrate reductase activity.